1994
DOI: 10.1002/mds.870090111
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of Parkinson's disease in a horticultural region of British Columbia

Abstract: We compared personal histories of 127 cases and 245 controls to identify possible environmental risk factors for idiopathic parkinsonism (IP). Of our controls, 121 had cardiac disease (CD) and 124 were randomly selected from electoral lists (voters). Using logistic regression and adjusting for sex and age, we ran separate analyses: IP versus CD and IP versus voters. A full occupational history was collected, as was known contact with all pesticides associated with the tree fruit sector of the agricultural indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
3
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 21 publications
4
97
3
1
Order By: Relevance
“…Similar to overall pesticide exposure, the population-based study of 250 incident cases mentioned above [316] found no association for occupational (men only) or home-based (men and women) exposure to herbicides. The other studies that found no association [131,292,299,301,315,325] were all smaller (100-150 cases); several did not adjust for smoking [292,299,301,315].…”
Section: Case-control Studiesmentioning
confidence: 97%
See 4 more Smart Citations
“…Similar to overall pesticide exposure, the population-based study of 250 incident cases mentioned above [316] found no association for occupational (men only) or home-based (men and women) exposure to herbicides. The other studies that found no association [131,292,299,301,315,325] were all smaller (100-150 cases); several did not adjust for smoking [292,299,301,315].…”
Section: Case-control Studiesmentioning
confidence: 97%
“…None of five such studies reported an association for exposure to fungicides overall [290,292,316,321,324]. The MSA study [324] reported a significant dose-response relationship between cumulative hours of fungicide exposure in men above 65 years (p for trend 0.02).…”
Section: Fungicide Exposurementioning
confidence: 99%
See 3 more Smart Citations